2020
DOI: 10.1111/ppl.13212
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the potential of EPS‐producing rhizobacteria with ACC‐deaminase activity to improve growth and physiology of maize under drought stress

Abstract: Rhizobacteria containing 1-aminocyclopropane-1-carboxylic aciddeaminase (ACC-deaminase) and exopolysaccharides (EPS) activity are important to induce stress tolerance in plants. The present study was conducted to screen and characterize plant growth-promoting rhizobacteria (PGPR) with ACC-deaminase and EPS-producing activity for improving maize growth under drought stress. Eighty-five rhizobacterial strains were isolated from the rain-fed areas, among those 69 isolates were able to utilize ACC and 31 strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…This finding was likely due to the general synergistic effects that allow members of Consortium C to optimize the use of resources 45 . In addition, a protective effect against water stress has also been observed in maize, pea and vetch plants treated with EPS-producing rhizobacteria 53 55 . It is known that EPSs provide a microenvironment that holds water and dries more slowly compared with the surrounding environment, thus protecting bacteria and roots of agriculturally relevant vegetables against desiccation 56 .…”
Section: Discussionmentioning
confidence: 91%
“…This finding was likely due to the general synergistic effects that allow members of Consortium C to optimize the use of resources 45 . In addition, a protective effect against water stress has also been observed in maize, pea and vetch plants treated with EPS-producing rhizobacteria 53 55 . It is known that EPSs provide a microenvironment that holds water and dries more slowly compared with the surrounding environment, thus protecting bacteria and roots of agriculturally relevant vegetables against desiccation 56 .…”
Section: Discussionmentioning
confidence: 91%
“…The EPS-producing bacteria Pseudomonas putida GAP-P45 can form a biofilm on the root surface, and plants inoculated with this strain show greater soil aggregation, more root-adhering soil, and high leaf RWC ( Sandhya et al., 2009 ). Nadeem et al. (2020) found that EPS-producing bacteria improved the photosynthetic rate, stomatal conductance, and other physiological characteristics of maize under drought stress.…”
Section: Improving Drought Resistance By Microbial Inoculationmentioning
confidence: 98%
“…Studies have shown that inoculation of tomato and pepper with Achromobacter ARV8, a PGPR that produces ACC deaminase, reduces ethylene levels and improves drought resistance of host plants ( Mayak et al., 2004 ). In addition, inoculation with ACC deaminase-producing PGPRs has positive effects on photosynthetic efficiency, stomatal conductance, water-use efficiency, transpiration rate, vapor pressure, chlorophyll content, and carbon content of maize plants under drought stress ( Danish et al., 2020 ; Nadeem et al., 2020 ). ACC deaminase-producing PGPRs also enhance osmotic adjustment and antioxidant defenses of host plants under drought stress ( Gowtham et al., 2020 ; Zarei et al., 2020 ).…”
Section: Improving Drought Resistance By Microbial Inoculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome‐wide association studies (GWAS), used for studying natural genetic variations, can identify genes and alleles involved in drought tolerance and metabolic regulation, which will pave the way for mapping and cloning gene loci regulating drought tolerance through controlled hormonal regulation, seed development and maintenance of water relations. In addition to current management practices, such as mineral fertiliser application and the use of compost (Hafez et al, 2020), the exogenous application of biostimulants (Nadeem et al 2020) and phytohormones (Khan et al, 2020) has been tested for their efficacy in improving water use efficiency and the mitigation of drought‐induced oxidative effects. Molecular genetic approaches and physio‐biochemical evaluations have revealed several key avenues for improving drought tolerance in plants, especially food crops as discussed by several researchers (Jabeen et al, 2020; Razik et al, 2020; Aleem et al, 2020).…”
mentioning
confidence: 99%